2009
DOI: 10.2217/pgs.09.17
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Apolipoprotein A5 Variants on Statin Treatment Efficacy

Abstract: Our results suggest that the APOA5 gene variants may play an important role in the pharmacogenetics of statin treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
24
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 22 publications
6
24
0
Order By: Relevance
“…The polymorphism of ApoA5 has been demonstrated to be tightly associated with ischemic stroke and hyperlipidemia [25]. Our data showed here that the SNP rs662799 affects the effectiveness of atorvastatin in all patients and in both Han and Uighur populations, which is in accordance with previous report in Caucasians population [26]. Thus the polymorphisms of APOA5 affect the effectiveness of atorvastatin.…”
Section: Discussionsupporting
confidence: 93%
“…The polymorphism of ApoA5 has been demonstrated to be tightly associated with ischemic stroke and hyperlipidemia [25]. Our data showed here that the SNP rs662799 affects the effectiveness of atorvastatin in all patients and in both Han and Uighur populations, which is in accordance with previous report in Caucasians population [26]. Thus the polymorphisms of APOA5 affect the effectiveness of atorvastatin.…”
Section: Discussionsupporting
confidence: 93%
“…11,19,20 The same region was also shown in large genome-wide association studies to be associated with baseline triglyceride and HDL-C levels. One limitation of our study—inherent in the sample set—is that previous use of other drug groups (statins, fibrates, niacin) prior to initiating the drug under investigation was not accounted for in the analyses.…”
Section: Discussionmentioning
confidence: 64%
“…8 We have previously shown that SNPs in the BUD13-APOA5 region affect HDL-C response to fibrate-statin combination therapy. 9,10 A recent study by Hubacek et al 11 showed that SNPs within the APOA5 gene region had an effect on LDL-C response to statins. In this study, we examined the association between common genetic variants in the APOA5-BUD13 gene region and change in LDL-C, HDL-C, and TG levels in response to statin therapy in the context of a longitudinal population study.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, drugs such as pravastatin and rotuvastatin are not susceptible to CYP inhibition, but are substrates of the a hepatic transporter and solute organic anion-transporting polypeptide (OATP) 1B1 (encoded by the SLCO1B1 gene) which is responsible for liver transportation of the statins 154 . Variants of the apolipoprotein, particularly the apo E and apo A5 also have their share in these processes [155][156][157][158] . Similarly, genetically impaired ABCG2 transporter efflux activity results in a marked increase in systemic exposure to various statins 159 .…”
Section: Genetics and Drug Therapy Of Coronary Artery Diseasementioning
confidence: 99%